IoT system of news by image for internal enterprise communication - Guimarães, Pedro Vitor de Sousa; Jucá, Sandro César Silveira; Pereira, Renata Imaculada Soares; Monteiro, Ayrton Alexsander Monteiro (Journal of Mechatronics Engineering, 2018)
This paper describes the use of a Linux embedded system for use in digital information and communication technology in order to generate image warnings using Internet of Things (IoT) prin- ciples. The proposed project generated a product, developed using concepts of project-based learning (ABP), called SECI (electronic internal communication system) that is accessed by students to view online warnings by distributed monitors and also by mobile devices connected to the Internet.